Conservancy : The Land Trust Movement in America - Brewer, Richard (Book collections on Project MUSE., 2003)
Brewer's information on the how and why of protecting land is enriched by his intimate knowledge of ecological systems, biodiversity, and the interconnectedness on human and non-human life forms." "Conservancy is a must-read volume for people interested in land conservation - including land trust members, volunteers, and supporters - as well as anyone concerned about land use and the environment."--Jacket